Immunogenicity and Safety of an Adjuvanted Herpes Zoster Subunit Vaccine Coadministered With Seasonal Influenza Vaccine in Adults Aged 50 Years or Older. (26th September 2017) - Schwarz, Tino F; Aggarwal, Naresh; Moeckesch, Beate; Schenkenberger, Isabelle; Claeys, Carine; Douha, Martine; Godeaux, Olivier; Grupping, Katrijn; Heineman, Thomas C; Fauqued, Marta Lopez; Oostvogels, Lidia; Van den Steen, Peter; et al.
Abstract : When the adjuvanted HZ subunit vaccine candidate was coadministered with a quadrivalent seasonal influenza vaccine, no interference in the immune responses were observed, and no safety concerns were identified. Abstract: Background: The immunogenicity and safety of an adjuvanted herpes zoster subunit (HZ/su) vaccine when coadministered with a quadrivalent seasonal inactivated influenza vaccine (IIV4) was investigated in a phase 3, open-label, randomized clinical trial in adults aged ≥50 years. Methods: Subjects were randomized 1:1 to receive either HZ/su (varicella zoster virus glycoprotein E; AS01B Adjuvant System) and IIV4 at day 0 followed by a second HZ/su dose at month 2 (coadministration group), or IIV4 at month 0 and HZ/su at months 2 and 4 (control group). The primary objectives were the HZ/su vaccine response rate in the coadministration group and the noninferiority of the antibody responses to HZ/su and IIV4 in the coadministration compared with the control group. Safety information was collected throughout the duration of the study. Results: A total of 413 subjects were vaccinated in the coadministration group and 415 in the control group. The HZ/su vaccine response rate in the coadministration group was 95.8% (95% confidence interval, 93.3%–97.6%) and the anti–glycoprotein E GMCControl/Coadmin ratio was 1.08 (.97–1.20). The primary noninferiority objectives were met. No safety concerns were observed. Conclusions: No interference in the immune responses to either vaccine was observed when the vaccines were coadministered, and no safety concerns were identified. Clinical Trials Registration: NCT01954251.